Comparison of Sleep Latency and Number of SOREMPs in the Home and Hospital With a Modified Multiple Sleep Latency Test: A Randomized Crossover Study. Issue 3 (May 2017) - Beiske, Kornelia K.; Sand, Trond; Rugland, Eyvind; Stavem, Knut
Abstract : Purpose: Comparison of mean sleep latencies and number of sleep-onset rapid eye movement periods (SOREMPs) between modified multiple sleep latency test (MSLT) performed in the unattended home and in-hospital laboratory setting. Methods: A randomized crossover single-blinded design. Thirty-four subjects referred to MSLT for suspected hypersomnia or narcolepsy were included. Participants were randomized to perform modified MSLT in the unattended home or in the hospital first. Scores in the two settings were compared using Wilcoxon signed-rank test or exact McNemar test. Agreement between home and hospital categorized mean sleep latency and number of SOREMPs was assessed using simple kappa (κ) and proportion agreement. Agreement between home and hospital mean sleep latency was assessed using a Bland–Altman plot and an intraclass correlation coefficient. Results: There was no difference between home and hospital assessment of mean sleep latency ( P = 0.86). Two or more SOREMPs were found more frequently on modified MSLTs performed at home compared with those at the hospital (7 and 2, respectively; P = 0.025). Agreement was moderate for categorized sleep latency (κ = 0.53) and fair for categorized SOREMPs (κ = 0.39) in the 2 settings. Analysis of mean sleep latency using intraclass correlation coefficient showed a very good agreement between the two settings. Conclusions: Group mean sleep latency for home modified MSLTs seems to be reliable compared with that for the attended sleep-laboratory setting. Higher rate of SOREMP in the unattended home suggests that napping in a familiar environment facilitates the transition into REM sleep. Further studies are needed to assess the normal limit, sensitivity, and specificity for SOREMP at home before the clinical utility of home-based napping can be determined.